Imaging the dynamics of magma propagation using radiated seismic intensity - Taisne, B. (2012)
At shallow depth beneath the Earth's surface, magma propagates through strongly heterogeneous volcanic material. Inversion of buoyancy and/or solidification have strong impacts on the dynamics of propagation without any change of magma supply. In this paper, we study the spatial and time evolution of magma intrusions using induced seismicity. We propose a new method based on ratio analysis of estimates of radiated seismic intensities recorded at different stations during seismic swarms. By applying this method to the January 2010 Piton de la Fournaise volcano eruption, we image complex dike propagation dynamics which strongly differ from a model of constant velocity dike propagation. We provide a new method to image in real time the dynamics of dike propagation and to infer the position of eruptive fissures